High-entropy (Hf0. 2Y0. 2W0. 2Mo0. 2Ti0. 2) C ceramic material containing rare earth element Y and preparation method thereof

Through powder metallurgy and induction heating pressure-free sintering technology, high entropy (Hf0.2Y0.2W0.2Mo0.2Ti0.2)C ceramic materials containing rare earth element Y were prepared, which solved the problem of poor oxidation resistance of existing ceramic materials at high temperatures, and achieved the preparation of high-purity, thermal stability and high-strength ceramic materials, which were suitable for large-scale mass production.

CN119822834AActive Publication Date: 2025-04-15INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311320568.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

Existing ultra-high temperature ceramic materials have poor oxidation resistance at high temperatures and are difficult to prepare on a large scale.

Method used

The powder metallurgy method combined with induction heating pressure-free sintering technology was used to prepare high-entropy (Hf0.2Y0.2W0.2Mo0.2Ti0.2)C ceramic material containing rare earth element Y, and uniform solid solution and high purity of the material are achieved through ball milling, cold pressing molding and ultra-high temperature sintering.

Benefits of technology

It realizes high purity, free phase, good thermal stability and high strength of ceramic materials, simplifies the preparation process, shortens the sintering cycle, and is suitable for large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822834A_ABST
    Figure CN119822834A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ultrahigh-temperature ceramic materials, in particular to a high-entropy (Hf < 0.2 > Y < 0.2 > W < 0.2 > Mo < 0.2 > Ti < 0.2 >) C ceramic material containing a rare earth element Y and a preparation method thereof. The material is prepared by adopting induction heating pressureless sintering, and the specific operation steps are as follows: 1) putting HfC, TiC, WC, Mo2C, YH2 and C powder into a nylon tank in proportion, adopting absolute ethyl alcohol as a medium, and obtaining powder slurry by adopting a wet ball milling method; 2) evaporating, drying and sieving the powder slurry to obtain HfC-TiC-WC-Mo2C-YH2-C mixed powder, and putting the HfC-TiC-WC-Mo2C-YH2-C mixed powder into a stainless steel mold for cold press molding; and (3) putting the formed green body into a graphite crucible, putting the graphite crucible and the formed green body into an ultra-high-temperature induction heating furnace together, and carrying out pressureless sintering under vacuum to obtain the (Hf < 0.2 > Y < 0.2 > W < 0.2 > Mo < 0.2 > Ti < 0.2 >) C ultra-high-temperature ceramic. The (Hf < 0.2 > Y < 0.2 > W < 0.2 > Mo < 0.2 > Ti < 0.2 >) C ultrahigh-temperature material prepared by the method has the advantages of high purity, simple and convenient preparation process flow, short preparation period and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ultra-high temperature ceramic materials, in particular to a high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material and preparation method thereof. Background Art

[0002] Ultra-high temperature ceramics refer to a class of non-oxide ceramic materials with a melting point of more than 3000℃, mainly including borides, carbides and nitrides of early transition metals. Carbides and nitrides have a series of unique properties, including high density, chemical thermal stability, corrosion resistance and extremely high melting point, making them ideal candidate material systems for ultra-high temperature thermal structures and thermal protection systems. Single-phase compounds composed of cations or anions of no less than four elements in equimolar or nearly equimolar ratios can be called high-entropy ceramics. These high-entropy ceramics have better mechanical properties, ionic conductivity, corrosion resistance and other properties than single-component ceramics. The emergence of ultra-high temperature high-entropy ceramics is expected to solve the problem of poor high-temperature oxidation resistance of single-phase ceramics, providing new ideas for the research of ultra-high temperature ceramics. It is one of the most promising ultra-high temperature thermal protection materials and has also received widespread attention. In particular, there has been no public report on the solid solution of rare earth element cations and related properties in high-entropy carbides at home and abroad. Therefore, the preparation of high-entropy ceramics containing rare earth element cations and the gradual development of their high-temperature and ultra-high temperature performance research also have good application prospects. Summary of the invention

[0003] The object of the present invention is to provide a high entropy (Hf) 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material and its preparation method, the method can quickly heat up to the sintering temperature, has the characteristics of simple operation process and short sintering cycle, and can meet the needs of large-scale batch preparation.

[0004] The technical solution of the present invention is as follows:

[0005] A high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, the chemical composition of high entropy ceramic material is (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C.

[0006] The high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, the preferred stoichiometric ratio of Hf, Ti, W, Mo, Y and C is 1:1:1:1:1:5.

[0007] The high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic materials, high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material achieves uniform solid solution of metal elements and rare earth element Y, and the particle size is uniform, 2 to 3 μm.

[0008] The high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 ) A method for preparing C ceramic material, the specific operation steps of the method are as follows:

[0009] 1) Weigh the required HfC, TiC, WC, and Mo according to the designed ratio. 2 C. YH 2 and C raw material powder, and pour them into the Si 3 N 4 In the nylon jar with grinding balls, add anhydrous ethanol as the medium, where: Si 3 N 4 The mass ratio of the grinding balls to the raw material powder is 2.8-3.5:1, and the mass ratio of the anhydrous ethanol to the raw material powder is 3-6:10;

[0010] 2) Fixing the nylon jar containing the raw material powder and the anhydrous ethanol medium in a planetary ball mill for wet ball milling mixing, the ball milling time is 8 to 12 hours, and the ball milling speed is 240 to 300 rpm;

[0011] 3) evaporating and drying the powder slurry obtained after wet ball milling, and sieving to obtain a mixed powder, wherein the mesh number of the sieve is 80 to 120 meshes;

[0012] 4) The obtained mixed powder is loaded into a stainless steel mold for cold pressing, the applied pressure range is 10 to 20 kN, the holding time is 3 to 10 minutes, and the diameter of the stainless steel mold is 8 to 20 mm;

[0013] 5) placing the cold pressed mixed powder in a graphite crucible, and placing it in an ultra-high temperature induction heating pressureless sintering furnace, and performing pressureless sintering in a vacuum, with a heating rate of 80 to 100° C. / min, a sintering temperature of 2400 to 2450° C., and a sintering time of 0.5 to 1 h;

[0014] 6) After the heat preservation is completed, the temperature is lowered to 800-1000°C at a rate of 60-100°C / min, and then cooled to room temperature with the furnace to obtain a high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic materials.

[0015] The high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material preparation method, in step 1), the average particle size of HfC powder is 0.8μm, and the powder purity is ≥99wt%; the average particle size of TiC powder is 1-3μm, and the powder purity is ≥99.5wt%; the average particle size of WC powder is 1-2μm, and the powder purity is ≥99.5wt%; Mo 2 The average particle size of C powder is 1-2 μm, and the powder purity is ≥99.5wt%; YH 2 The average particle size of the powder is 1-2 μm, and the powder purity is ≥99wt%; the average particle size of the C powder is 1-2 μm, and the powder purity is ≥99.9wt%.

[0016] The design concept of the present invention is:

[0017] High entropy (Hf) containing rare earth element Y was prepared by induction heating pressureless sintering. 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2)C ceramic materials, because more components are introduced into high entropy carbide ceramics, especially the first time that rare earth elements are dissolved in the cation position of carbide, resulting in atomic size differences in the unit cell, resulting in a large amount of lattice distortion, which increases the resistance to dislocation movement, making it very difficult to slide under the action of external force, greatly improving the strength and hardness of the ceramics. At the same time, the change in thermal resistance caused by the increase in defects in the ceramics further improves the thermal conductivity of the ceramics. Lattice distortion limits the movement of phonons, and for high entropy carbide ceramics, the contribution rate of phonons in thermal conductivity increases, thereby improving the thermal conductivity of high entropy carbide ceramics. And (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C solid solution ceramics are predicted to have ultra-high melting points and good thermal stability through first-principles calculations, and have great application prospects in ultra-high temperatures.

[0018] The advantages and beneficial effects of the present invention are:

[0019] 1. The novel high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, using ultra-high temperature induction heating equipment for pressureless sintering, the heating and cooling rate is fast, the preparation process is simple and easy, and the preparation cycle is short.

[0020] 2. The high entropy (Hf) containing rare earth element Y of the present invention 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, the prepared samples have good purity and no impurities.

[0021] 3. The new high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic block material, the prepared material has good thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The (Hf prepared in Examples 1 to 5 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )X-ray diffraction spectrum of C ceramic material, where the horizontal axis 2θ is the diffraction angle (°).

[0023] Figure 2 The high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 ) Surface morphology photograph (a) and energy spectrum (b) of C ceramic material (Example 2).

[0024] FIG. 3 is a high entropy (Hf) containing rare earth element Y prepared by the present invention 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 ) Surface morphology photograph (a) and energy spectrum (b) of C ceramic material powder (Example 3).

[0025] Figure 4 (Hf prepared in Example 3 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material powder EDS element surface distribution analysis diagram (the top figure is (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic morphology; the following figures are C, Hf, Mo, Ti, W, Y element surface distribution analysis diagrams respectively).

[0026] Figure 5 (Hf prepared in Example 4 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ultra-high temperature ceramic bulk material measured thermogravimetric (TG) and differential scanning calorimetry (DSC) curves. In the figure, the horizontal axis Temperature is the temperature (℃), and the vertical axis DSC is the heat flow rate (mW / mg). DETAILED DESCRIPTION

[0027] In the specific implementation process, the present invention adopts a powder metallurgy method to prepare a high entropy (Hf) containing rare earth element Y by pressureless sintering. 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 ) C ceramic material, the specific operation steps of the method are as follows:

[0028] 1) Weigh the required HfC, TiC, WC, and Mo according to the designed ratio.2 C. YH 2 and C raw material powders are poured into the Si 3 N 4 The samples were placed in a nylon jar with grinding balls to ensure full contact and uniform mixing. Anhydrous ethanol was added as the ball milling medium. 3 N 4 The mass ratio of the grinding balls to the raw material powder is 2.8-3.5:1, and the mass ratio of the anhydrous ethanol to the raw material powder is 3-6:10;

[0029] Among them, the average particle size of HfC powder is 0.8μm, and the powder purity is ≥99wt%; the average particle size of TiC powder is 1-3μm, and the powder purity is ≥99.5wt%; the average particle size of WC powder is 1-2μm, and the powder purity is ≥99.5wt%; 2 The average particle size of C powder is 1-2 μm, and the powder purity is ≥99.5wt%; YH 2 The average particle size of the powder is 1-2 μm, and the powder purity is ≥99wt%; the average particle size of the C powder is 1-2 μm, and the powder purity is ≥99.9wt%.

[0030] 2) The nylon jar containing the raw material powder and the anhydrous ethanol medium is fixed in a planetary ball mill for ball milling and mixing, the purpose of which is to reduce the particle size of the powder and expose the fresh active surface of the powder to facilitate subsequent pressureless sintering. The ball milling time is 8 to 12 hours and the ball milling speed is 240 to 300 rpm;

[0031] 3) The powder slurry obtained after mixing and crushing is evaporated and dried, and sieved to obtain a mixed powder, and the mesh number of the sieve is 80-120 mesh;

[0032] 4) The obtained mixed powder is loaded into a stainless steel mold for cold pressing, the applied pressure range is 10 to 20 kN, the holding time is 3 to 10 minutes, and the diameter of the stainless steel mold is 8 to 20 mm;

[0033] 5) placing the cold pressed mixed powder in a graphite crucible, and placing it in an ultra-high temperature induction heating pressureless sintering furnace, and performing pressureless sintering in a vacuum, with a heating rate of 80 to 100° C. / min, a sintering temperature of 2400 to 2450° C., and a sintering time of 0.5 to 1 h;

[0034] 6) After the heat preservation is completed, the temperature is lowered to 800-1000°C at a rate of 60-100°C / min, and then cooled to room temperature with the furnace to obtain a high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic materials.

[0035] The ceramic material includes the phase (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C. The prepared sample realizes uniform solid solution of metal elements and rare earth elements at the carbide cation position, and the particle size is uniform, 2 to 3 μm, and the Hf, Ti, W, Mo, Y, and C elements contained therein are uniformly distributed. Further, the ceramic material prepared by the present invention is verified to have uniform composition through examples.

[0036] The present invention is further described in detail below by examples and drawings. However, these examples shall not be interpreted as limiting the scope of protection of the present invention, and all changes within the basic idea of ​​the technical solution of the present invention or essentially equivalent to the technical solution of the present invention are within the scope of protection of the present invention.

[0037] Example 1

[0038] First, 19.05 g of HfC powder with a particle size of 0.8 μm, 5.99 g of TiC powder with a particle size of 1 μm, and 1 μm of Mo 2 C powder 10.20g, 1μm YH 2 9.09 g of powder, 19.58 g of 1 μm WC powder and 1.80 g of 1 μm C powder (the obtained (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C material Hf, Ti, W, Mo, Y, C (the stoichiometric ratio is 1:1:1:1:1:5) is placed in a nylon ball mill and ball milled for 12 hours. After evaporation and drying, it is sieved through an 80-mesh sieve to obtain a mixed ceramic powder. Then, it is loaded into a stainless steel mold with a diameter of 20 mm and cold pressed at 15kN for 5 minutes. Then, the cold-pressed mixed powder is placed in a graphite crucible and placed in an induction heating furnace for pressureless sintering in a vacuum. It is heated to 2400°C at a heating rate of 80°C / min and kept warm for 0.5h. After the insulation is completed, the temperature is reduced to 1000°C at a cooling rate of 60°C / min, and air-cooled to room temperature to obtain (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ultra-high temperature ceramic material.

[0039] like Figure 1 As shown, the high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti0.2 )C ceramic material X-ray diffraction spectrum. From the diffraction spectrum, it can be seen that after high temperature sintering, the initial materials HfC, TiC, WC, Mo 2 C. YH 2 and C to form (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C, and the characteristic peaks of HfC, TiC, WC, MoC, and YC are fused to achieve solid solution, and a single-phase high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C phase, the sample is relatively pure and has no impurity peaks.

[0040] Example 2

[0041] First, 9.53 g of HfC powder with a particle size of 0.8 μm, 2.99 g of TiC powder with a particle size of 1 μm, and 1 μm of Mo 2 C powder 5.10g, 1μm YH 2 4.55 g of powder, 9.79 g of 1 μm WC powder and 0.90 g of 1 μm C powder (the obtained (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C material Hf, Ti, W, Mo, Y, C (the stoichiometric ratio is 1:1:1:1:1:5) is placed in a nylon ball mill and ball milled for 12 hours. After evaporation and drying, it is sieved through an 80-mesh sieve to obtain a mixed ceramic powder. Then, it is loaded into a stainless steel mold with a diameter of 20 mm and cold pressed at 15kN for 5 minutes. Then, the cold-pressed mixed powder is placed in a graphite crucible and placed in an induction heating furnace for pressureless sintering in a vacuum. It is heated to 2400°C at a heating rate of 90°C / min and kept warm for 0.5h. After the insulation is completed, the temperature is reduced to 1000°C at a cooling rate of 60°C / min, and air-cooled to room temperature to obtain (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ultra-high temperature ceramic material.

[0042] like Figure 2 As shown in Table 1, the high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2)C ceramic material surface morphology photos, energy spectrum and each element content, it can be seen that the element content of the obtained material is in line with expectations and there is no element escape and impurity elements, and by Figure 2 It can be seen that (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C Ultra-high temperature ceramic material particles are uniform in size and evenly distributed.

[0043] Table 1 High entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )CContent of each element in ceramic material

[0044] Element C Ti Y Mo Hf W Weight % 9.81 6.77 13.40 12.81 30.05 27.16 Atomic% 52.41 9.07 9.67 8.57 10.80 9.48

[0045] Example 3

[0046] First, 6.35 g of HfC powder with a particle size of 0.8 μm, 2.00 g of TiC powder with a particle size of 1 μm, and 1 μm of Mo 2 C powder 3.40g, 1μm YH 2 3.03 g of powder, 6.53 g of 1 μm WC powder and 0.60 g of 1 μm C powder (the obtained (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C material Hf, Ti, W, Mo, Y, C (the stoichiometric ratio is 1:1:1:1:1:5) is placed in a nylon ball mill and ball milled for 12 hours. After evaporation and drying, it is sieved through an 80-mesh sieve to obtain a mixed ceramic powder. Then, it is loaded into a stainless steel mold with a diameter of 20 mm and cold pressed at 15kN for 5 minutes. Then, the cold-pressed mixed powder is placed in a graphite crucible and placed in an induction heating furnace for pressureless sintering in a vacuum. It is heated to 2450°C at a heating rate of 100°C / min and kept warm for 0.5h. After the insulation is completed, the temperature is reduced to 1000°C at a cooling rate of 60°C / min, and air-cooled to room temperature to obtain (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ultra-high temperature ceramic material.

[0047] As shown in Figure 3- Figure 4 As shown in Table 2, the high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti0.2 )C ceramic material powder element surface distribution analysis diagram. It can be seen from the figure that Hf element, Ti element, W element, Mo element, Y element, and C element are evenly distributed in the microstructure, and there is no other impurity phase in the sintered body.

[0048] Table 2 High entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C The content of each element in the powder of ceramic material

[0049] Element C Ti Y Mo Hf W Weight % 7.24 6.90 15.89 13.59 26.65 29.72 Atomic% 43.79 10.44 12.96 10.27 10.83 11.72

[0050] Example 4

[0051] First, 28.58 g of HfC powder with a particle size of 0.8 μm, 8.99 g of TiC powder with a particle size of 1 μm, and 1 μm of Mo 2 C powder 15.30g, 1μm YH 2 13.64 g of powder, 29.37 g of 1 μm WC powder and 2.70 g of 1 μm C powder (the obtained (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C material Hf, Ti, W, Mo, Y, C (the stoichiometric ratio is 1:1:1:1:1:5) is placed in a nylon ball mill and ball milled for 12 hours. After evaporation and drying, it is sieved through an 80-mesh sieve to obtain a mixed ceramic powder. Then, it is loaded into a stainless steel mold with a diameter of 20 mm and cold-pressed at 15kN for 5 minutes. Then, the cold-pressed mixed powder is placed in a graphite crucible and placed in an induction heating furnace for pressureless sintering in a vacuum. It is heated to 2450°C at a heating rate of 80°C / min and kept warm for 0.5h. After the insulation is completed, the temperature is reduced to 1000°C at a cooling rate of 60°C / min, and air-cooled to room temperature to obtain (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ultra-high temperature ceramic material.

[0052] like Figure 5 As shown, the high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 TG and DSC curves of 19.66 mg powder of C ultrahigh temperature ceramic bulk material obtained by heating from 30°C to 1600°C at 10°C / min in argon atmosphere. Figure 5 The TG curve shows that the mass of the sample changes very little during the heating process, within 1.4 mg or 7.12%. And the DSC curve shows that the extrapolated starting temperature of the endothermic peak of 1250℃~1500℃ during the heating process is 1280℃, and the peak temperature is 1471℃. Both temperatures are very high, indicating that its phase transition temperature is very high. The combination of the DSC curve and the TG curve shows that the thermal stability of the prepared material is high.

[0053] The results of the examples show that the high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ultra-high temperature ceramic materials not only have uniform particle size, but also have relatively pure materials, no impurities and high thermal stability. In addition, they also have the advantages of simple preparation process and short preparation cycle.

Claims

1. A high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, characterized in that The chemical composition of high entropy ceramic materials is (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C.

2. The high entropy (Hf) containing rare earth element Y according to claim 1. 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, characterized in that The preferred stoichiometric ratio of Hf, Ti, W, Mo, Y and C is 1:1:1:1:1:

5.

3. The high entropy (Hf) containing rare earth element Y according to claim 1. 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material, characterized in that High Entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic material achieves uniform solid solution of metal elements and rare earth element Y, and the particle size is uniform, 2 to 3 μm.

4. A high entropy (Hf) containing rare earth element Y as claimed in any one of claims 1 to 3. 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C A method for preparing a ceramic material, characterized in that: The specific steps of this method are as follows: 1) Weigh the required HfC, TiC, WC, Mo2C, YH2 and C raw material powders according to the designed proportion, and pour them into the nylon jar containing Si3N4 grinding balls in the manner of "more-less-more-less-more-less", and add anhydrous ethanol as the medium, wherein: the mass ratio of Si3N4 grinding balls to raw material powders is 2.8-3.5:1, and the mass ratio of anhydrous ethanol to raw material powders is 3-6:10; 2) Fixing the nylon jar containing the raw material powder and the anhydrous ethanol medium in a planetary ball mill for wet ball milling mixing, the ball milling time is 8 to 12 hours, and the ball milling speed is 240 to 300 rpm; 3) evaporating and drying the powder slurry obtained after wet ball milling, and sieving to obtain a mixed powder, wherein the mesh number of the sieve is 80 to 120 meshes; 4) The obtained mixed powder is loaded into a stainless steel mold for cold pressing, the applied pressure range is 10 to 20 kN, the holding time is 3 to 10 minutes, and the diameter of the stainless steel mold is 8 to 20 mm; 5) placing the cold pressed mixed powder in a graphite crucible, and placing it in an ultra-high temperature induction heating pressureless sintering furnace, and performing pressureless sintering in a vacuum, with a heating rate of 80 to 100° C. / min, a sintering temperature of 2400 to 2450° C., and a sintering time of 0.5 to 1 h; 6) After the heat preservation is completed, the temperature is lowered to 800-1000°C at a rate of 60-100°C / min, and then cooled to room temperature with the furnace to obtain a high entropy (Hf 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C ceramic materials.

5. The high entropy (Hf) containing rare earth element Y according to claim 4. 0.2 Y 0.2 W 0.2 Mo 0.2 Ti 0.2 )C A method for preparing a ceramic material, characterized in that: In step 1), the average particle size of HfC powder is 0.8 μm, and the powder purity is ≥99wt%; the average particle size of TiC powder is 1-3 μm, and the powder purity is ≥99.5wt%; the average particle size of WC powder is 1-2 μm, and the powder purity is ≥99.5wt%; The average particle size of Mo2C powder is 1-2μm, and the powder purity is ≥99.5wt%; the average particle size of YH2 powder is 1-2μm, and the powder purity is ≥99wt%; the average particle size of C powder is 1-2μm, and the powder purity is ≥99.9wt%.

Citation Information

Patent Citations

  • Carbide high-entropy ceramic precursor containing rare earth, high-entropy ceramic and preparation method

    CN111303581A

  • High-entropy boride reinforced B4C composite ceramic and in-situ synthesis method thereof

    CN115872749A

  • Production of sintered borides carbides nitrides and silicides

    GB1324282A

  • Hard metals and method for producing the same

    US20230052721A1

  • High-entropy carbide ceramic and rare earth-containing high-entropy carbide ceramic, fibers and precursors thereof, and methods for preparing the same

    US20230088418A1